Pengaruh Pengawasan Keuangan Daerah, Akuntabilitas, dan Transparansi Pengelolaan Keuangan Daerah Terhadap Kinerja Pemerintah - Muhammad Nasrul Amali; Eko Darmawan Suwandi (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi, 2021)
This study was aimed at finding out (1) the effect of local finance supervision on Local Government performance, (2) the effect of local finance management accountability on Local Government performance, (3) the effect of local finance management transparency on Local Government performance, and (4) the effect of local finance supervision, local finance management accountability and local finance management transparency on Local Government performance. This study was conducted in the SKPD of Kebumen Regency using a population of 52 people. The data used in the supervision sector were of qualitative types and their source was a primary source. The data were collected using questionnaire. The data were analyzed using multiple regression analysis aided by SPSS program of version 25.00. This study was aimed at finding out (1) Regional financial supervisor has not effect on the performance of the Kebumen Regency government, (2) financial management accountability has not effect on the performance of the Kebumen Regency government, (3) the transparency of financial management has not effect on the performance of the Kebumen Regency government,(4) the local finance supervision, accountability and transparency in the finance management have a effect on the Local Government of Buleleng Regency performance.